Romani American history: Historical absences and their consequences - ANN OSTENDORF (Romani Studies)
American historians have created an historical absence by ignoring Romani people’s presence in evidence from the past. The origins of this “absence-ing” are multifaceted and interrelated, but fundamentally stem from the continued influence of out-of-date and unprofessional ways of thinking and knowing. Examining and understanding “absence-ing” requires a consideration of the nature of the discipline of history as well as a history of the missing historicization of Romani Americans. The consequences of the “absence-ing” of Romani people from American histories have negatively and distinctively influenced four different groups of people: historians of the Americas; historians of Romani people in Europe; Romani studies scholars of the Americas who are not historians; and Romani Americans. The harm that each of these four groups experiences builds upon and influences the others. Epistemic injustice is thus perpetuated in linked ways. This article was published open access under a CC BY licence: https://creativecommons.org/licences/by/4.0.